Aspectual grammar and past-time reference - Michaelis, Laura A., 1964- (Routledge studies in Germanic linguistics, 1998)
This study presents a semantic framework for analysing all aspectual constructions in terms of the event state distinction, and describes the grammatical expression of aspectual meaning in terms of a theory of grammatical constructions.